Geometry of the semicircular canals of the chinchilla (Chinchilla laniger) - Hullar, Timothy E. (2006)
The orientations of the semicircular canals determines the response of the canals to head rotations and, in turn, the brain’s ability to interpret those motions. The geometry of chinchillas’ semicircular canals has never been reported. Volumetric representations of three chinchilla skulls were generated using a microCT scanner. The centroids of each semicircular canal lumen were identified as they passed through the image slices and were regressed to a plane. Unit vectors normal to the plane representing canal orientations were used to calculate angles between canal pairs. Pitch and roll maneuvers required to bring any canal into the horizontal plane for physiologic investigation were calculated. The semicircular canals of the chinchilla were found to be relatively planar. The horizontal canal was found to be oriented 55.0° anteriorly upward. Pairs of ipsilateral chinchilla canals were not orthogonal and contralateral synergistic pairs were not parallel. Despite this arrangement, the canal plane unit normal vectors were organized to respond with approximately equal overall sensitivity to rotations in any direction. The nonorthogonal chinchilla labyrinth may provide an opportunity to determine whether the frame of reference used by the central vestibular and oculomotor system is based on directions of afferent maximum sensitivity or prime directions.